2013
DOI: 10.3109/0142159x.2012.735381
|View full text |Cite
|
Sign up to set email alerts
|

The transition to hospital consultant and the influence of preparedness, social support, and perception: A structural equation modelling approach

Abstract: These findings illustrate the relevance of generic competencies for new hospital consultants. Furthermore, social support facilitates this intense and stressful stage within the medical career.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 35 publications
3
84
0
Order By: Relevance
“…Although new consultants are generally satisfied with their training in clinical skills (McKinstry et al 2005;Beckett et al 2006), they feel less prepared for their non-clinical tasks, in particular, in the area of management and (financial) organization (Higgins et al 2005;Beckett et al 2006;Morrow et al 2009;Berkenbosch et al 2011). As a result, such tasks are experienced as stressful (Beckett et al 2006) and there is evidence to suggest that insufficient training in these tasks is related to stress and burnout among new consultants (Westerman et al 2013a). A better understanding of the shortcomings new consultants experience in their preparation for independent practice could help to prevent the negative societal, personal and financial consequences of such problematic transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Although new consultants are generally satisfied with their training in clinical skills (McKinstry et al 2005;Beckett et al 2006), they feel less prepared for their non-clinical tasks, in particular, in the area of management and (financial) organization (Higgins et al 2005;Beckett et al 2006;Morrow et al 2009;Berkenbosch et al 2011). As a result, such tasks are experienced as stressful (Beckett et al 2006) and there is evidence to suggest that insufficient training in these tasks is related to stress and burnout among new consultants (Westerman et al 2013a). A better understanding of the shortcomings new consultants experience in their preparation for independent practice could help to prevent the negative societal, personal and financial consequences of such problematic transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Ochsmann [2] reported that among 637 German residents, adverse work characteristics, such as work-related support, availability of postgraduate training possibilities and overtime, increase the risk of thinking about leaving clinical care. Furthermore, Westerman et al [13] showed for transition from specialty training to a position as hospital consultant that social support facilitates the process through this phase . Among later-career doctors, work characteristics also determine intention to leave clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…This study used self-reported measures, which have the potential for bias 11. However, the questionnaires were matched to pre and post perception.…”
Section: Limitationsmentioning
confidence: 99%